THE ORIGIN OF MICROBIOLOGY AND ITS DIFFERENCES WITH BIOLOGY - Suleymanova Marg`uba Kenjaboyevna (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the origin of microbiology, the fact that the first systematic system of microorganisms applies to Danish Myuller, microbiology cannot be seen with a very small, simple eye.